Spatial and Temporal Variability of Aerosol Vertical Distribution Based on Lidar Observations: A Haze Case Study over Jinhua Basin - Wanchun Zhang; Mortier Augustin; Ying Zhang; Zhengqiang Li; Hua Xu; Dong Liu; Zhenzhu Wang; Yuhuan Zhang; Yan Ma; Fengxia Zhang; Yang Lv (Advances in Meteorology)
The impacts of haze emphasized significance of hazards for human activities and importance of observations of aerosol vertical distribution. This study aimed to analyze the aerosol vertical distribution during a haze case at temporal and spatial aspects, using space-borne and ground-based Lidar observations over Jinhua Basin, Zhejiang province, as well as the Hybrid Single-Particle Lagrangian Integrated Trajectory (HSPLIT) model and optical situ monitoring at Jinhua site. The results highlight three pollution peaks above the surface located in the upper and lower boundary layer in Jinhua Basin. The trajectory analysis shows the pollutants inside and outside the planetary boundary layer from different sources. Planetary boundary layer height (PBLH) obtained from the space-borne Lidar observations was compared with that from ground-based Lidar observations. The absolute error between the two instruments is about 0.193 km. It is illustrated that the space-borne Lidar is an effective instrument for obtaining regional aerosol pollution in vertical section. Pollution transport near the ground is closely related with the terrain condition.